Dietary fiber intake and hippocampal gray matter volume: an exploratory cross-sectional study in healthy adults - Pallapothu, Raghav; Newman-Norlund, Roger D.; Gibson, Makayla; Kannan, Pranesh Rajesh; Pallapothu, Sriya; Rorden, Chris; Bonilha, Leonardo; Fridriksson, Julius (Frontiers in Nutrition, 2025)
IntroductionAlzheimer’s disease and related dementia (ADRD) are associated with significance societal costs and economic burdens. Prior research has found that ADRD is associated with decreases in cortical gray matter volume (GMV) in the hippocampus.MethodsThis exploratory cross-sectional study investigates the relationship between total dietary fiber concentration and regional GMV in a cohort of 190 healthy adults aged 20 to 79 years who completed the 2015 National Health Interview Survey Supplement and T1-weighted magnetic resonance imaging (MRI) as part of the University of South Carolina’s Aging Brain Cohort (ABC) study. Hippocampal gray matter volume was quantified using the CAT12 voxel-based morphometry toolbox, using Spearman’s rank order correlation coefficient.ResultsOur exploratory analysis revealed a significant positive correlation between dietary fiber consumption and GMV in the right hippocampus and right parahippocampal gyrus, when controlling for age, race, sex, and median household income within participant zip code. Dietary fiber was also correlated with the MoCA attention/concentration and language subscores.DiscussionThese data are compatible with the hypothesis that dietary fiber may exert neuroprotective effects, and this may have implications for dietary recommendations aimed at reducing the risk of Alzheimer’s disease and related dementias.